Knowledge, attitude and practice (KAP) of pet owners towards rabies in cats - Nor Syakirah M Bakri
The latest rabies outbreak in Malaysia has caused major public health concerns, particularly in the Klang Valley. There have been human deaths due to being bitten by rabid dogs. Cats are also a susceptible host for rabies virus and cases have been reported elsewhere on a threat of rabid cats to humans. This study aimed to assess the knowledge, attitude and practice (KAP) regarding feline rabies among pet owners in Malaysia. This study focuses on the pet owners’ general knowledge on the rabies infection that could be transmitted to their cats. A cross-sectional online survey was conducted among pet owners in Malaysia between 14th September 2022 until 2nd October 2022. There were 400 respondents via an online questionnaire in Google Form. The data was analysed using IBM SPSS Statistics and descriptive statistics to determine the level of knowledge, attitude and practice on rabies. The analyses indicated that about 89% (n=357) of pet owners knew about rabies and 69% (n=276) were aware that cats can be infected by rabies. The overall knowledge of the respondents towards rabies in cats indicated that only 22% (n=88) had poor knowledge. In addition, the respondents’ attitude towards rabies showed that 60% (n=240) had a moderate attitude and 75% (n=280) showed moderate practice. The awareness of rabies in cats should be a continuous effort to ensure the knowledge of the disease, and its control and prevention reaching to many more pet owners specifically and the public in general.